Effects of yellow mealworm (Tenebrio molitor) larvae meal on the growth performance, serum biochemical parameters and caecal metabolome in broiler chickens - Teng Jiang; Xiaoyu Zhao; Haiying Li; Lihua Zhang; Bihui Tang; Yawen Ding; Yingping Wu (Italian Journal of Animal Science)
The goal of this study was to evaluate the effects of Tenebrio molitor (TM) larvae meal on the growth performance, serum biochemical parameters and caecal metabolome of broiler chickens. A total of 600 1-d-old male Liangfenghua broilers were randomly assigned to five equal groups with 5 replicates and 24 birds in each replicate. The dietary treatments were as follows: the control group (TM0 group) was fed a basal diet, and the experimental groups were fed experimental diets in which 3% (TM3 group), 5% (TM5 group), 7% (TM7 group) and 9% (TM9 group) TM larvae meal included in the basal diet, respectively. The feeding period was 70 d. The results showed that body weight (BW) and average daily gain (ADG) significantly increased (p < 0.05) in response to dietary 3% TM larvae meal supplementation at the age of 70 d. Serum concentrations of triglyceride (TG) and serum activity of aspartate aminotransferase (AST) decreased (p < 0.05) in 3% TM larvae meal-fed broilers. UHPLC-MS/MS-based metabolomics analysis revealed that a total of 55 significantly different metabolites were obtained in the caecal contents of dietary TM larvae meal supplemented broilers. The relative contents of 28 metabolites such as trans-4-hydroxy-L-proline, thymine and retinoic acid were significantly up-regulated (FC > 1.5) and the relative contents of 27 metabolites like prostaglandin F2α, glucocorticoids and prostaglandin E2 were significantly down-regulated (FC < 0.667) in the TM3 group. The main altered pathways were clustered into arachidonic acid metabolism, primary bile acid metabolism and propionic acid metabolism. In conclusion, the results indicated that supplementation of 3% TM larvae meal can improve growth performance, reduce the activity of serum AST and the content of TG, and regulation of the pathways of lipid, amino acid, and sugar metabolism in the caecum of broilers by improving nutrient digestion and absorption.